Di-n-butyl[N′-(3-methoxy-2-oxidobenzylidene)-N-phenylcarbamohydrazonothioato]tin(IV): crystal structure, Hirshfeld surface analysis and computational study - Enis Nadia Md Yusof,; Kwong, Huey Chong *; Thiruventhan, K.; Ravoof, Thahira Begum S. A.; Tiekink, Edward R. T. * (International Union of Crystallography, 2021)
The title diorganotin Schiff base derivative, [Sn(C4H9)2(C15H13N3O2S)], features a penta-coordinated tin centre defined by the N,O,S-donor atoms of the dianionic Schiff base ligand and two methylene-C atoms of the n-butyl substituents. The resultant C2NOS donor set defines a geometry intermediate between trigonal–bipyramidal and square-pyramidal. In the crystal, amine-N—HO(methoxy) hydrogen bonding is found in a helical, supramolecular chain propagating along the b-axis direction. The chains are assembled into a layer parallel to (101) with methylene-C—H(phenyl) interactions prominent; layers stack without directional interactions between them. The analysis of the calculated Hirshfeld surface showed the presence of weak methylene-C—H(phenyl) interactions and short HH contacts in the inter-layer region. Consistent with the nature of the identified contacts, the stabilization of the crystal is dominated by the dispersion energy term.